The Effectiveness of Regional Innovation Policies in Increasing Local Government Innovation: A Study on the Regional Innovation Index Program - I Gede Made Suwanda; Endang Try Setyaning; Karno (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the effectiveness of the Regional Innovation Index (Indeks Inovasi Daerah/IID) policy managed by the Regional Policy Strategy Agency (Badan Strategi Kebijakan Dalam Negeri/BSKDN) of the Ministry of Home Affairs in encouraging regional government innovation in Indonesia. Using a qualitative descriptive approach with data collection techniques of in-depth interviews with eight key informants (BSKDN officials and regional government representatives), observation, and documentation study, this research applies the policy effectiveness framework of Subarsono covering four dimensions: input, process, output, and outcome. The results show that from the policy design perspective, the IID has a strong regulatory framework (Law No. 23/2014, Government Regulation No. 38/2017, Minister of Home Affairs Regulation No. 104/2023), structured assessment indicators, and an award mechanism (Innovative Government Award/IGA) that functions as an effective non-fiscal incentive. In the process aspect, implementation runs systematically through the stages of data collection, verification, validation, assessment, and publication of results. However, the effectiveness of the IID is still hindered by three main factors: (1) disparities in human resource and institutional capacity across regions, (2) inequality in budget support, (3) dominance of administrative compliance orientation over innovation substance. Consequently, although quantitative output has increased dramatically (from 576 innovations in 2017 to 31,719 innovations in 2024 with 529 out of 546 regions participating), substantive outcomes such as improved public service quality and innovation sustainability have not been optimal. This study recommends strengthening quality assurance mechanisms, developing an innovation impact evaluation system, and reinforcing the inter-regional innovation learning ecosystem.